Role of Individual Basal Ganglia Nuclei in Force Amplitude Generation - Spraker, Matthew B. (2007)
The basal ganglia-thalamo-cortical loop is an important neural circuit that regulates motor control. A key parameter that the nervous system regulates is the level of force to exert against an object during tasks such as grasping. Previous studies indicate that the basal ganglia do not exhibit increased activity with increasing amplitude of force, although these conclusions are based mainly on the putamen. The present study used functional magnetic resonance imaging to investigate which regions in the basal ganglia, thalamus, and motor cortex display increased activity when producing pinch-grip contractions of increasing force amplitude. We found that the internal portion of the globus pallidus (GPi) and subthalamic nucleus (STN) had a positive increase in percent signal change with increasing force, whereas the external portion of the globus pallidus, anterior putamen, posterior putamen, and caudate did not. In the thalamus we found that the ventral thalamic regions increase in percent signal change and activation volume with increasing force amplitude. The contralateral and ipsilateral primary motor/somatosensory (M1/S1) cortices had a positive increase in percent signal change and activation volume with increasing force amplitude, and the contralateral M1/S1 had a greater increase in percent signal change and activation volume than the ipsilateral side. We also found that deactivation did not change across force in the motor cortex and basal ganglia, but that the ipsilateral M1/S1 had greater deactivation than the contralateral M1/S1. Our findings provide direct evidence that GPi and STN regulate the amplitude of force output. These findings emphasize the heterogeneous role of individual nuclei of the basal ganglia in regulating specific parameters of motor output.